Table of Content - - (Journal of Humanities & Social Sciences, 2025)
Table of Content:1. Agricultural cooperatives as a mechanism to strengthen the solidarity and social economy  and achieve territorial development in the Tafrata Plain in northeastern MoroccoDr. Smail Bouguelba ,Dr. El-Kallouchi Mohamed2. Analysis of Annual and Monthly Temperature Fluctuations in Makkah  for the Period 1950–2023Ms. Njoud Abd Alaziz Alamro ,Prof. Hussein Ahmed Almohamad3. The Role of Non-Governmental Organizations in Achieving Sustainable Social Development  In light of Vision 2030 : A Survey study of Workers in the Social Development Committees  in Taif GovernorateMr. Ali Jamaan sahlan Alghamdi4. Sustainable development discourse on the environmental crisis in an unequal world A Socio-critical readingDr. Aida Elhadi Ben Kraiem5. The legal purposes and their impact on protecting the Muslim from deviationMr. Housin Mohammed Agha6. Books of classes and translations among the Arabs from The Second Century AH - Fourteenth Century AHDr. Maha Mohammed Alqahtani7. Spatial analysis of the distribution of banks and commercial banks in Hail, a study using geographic information systems (GIS)Ms. Maryam Radhi Sayah Alshamri
Keywords: Journal of Human and Social Sciences